Effects of freeze–thawing cycles on desorption behaviors of PAH-contaminated soil in the presence of a biosurfactant: a case study in western Canada. Issue 6 (26th May 2017) - Yao, Y.; Huang, G. H.; An, C. J.; Cheng, G. H.; Wei, J.
Abstract : The combined effects of freeze–thawing cycles and surfactant can inhibit the sequestration of phenanthrene in soil. Abstract : Many regions in Canada are facing increasing environmental threats posed by oil and gas exploitation and transportation. These contaminated lands are inevitably subjected to seasonal and diurnal freeze–thawing cycles (FTCs). However, knowledge about the effect of FTCs on the behaviours of hydrophobic contaminants during the aging process of soil is limited. This study investigated the desorption characteristics of phenanthrene in aging soils in the presence of the biosurfactant rhamnolipid under diurnal and seasonal FTC treatments. It was found that the presence of rhamnolipid in soil during the aging process was able to increase the desorption efficiency of phenanthrene. In the presence of rhamnolipid above 100 mg L −1, FTCs could inhibit the sequestration of phenanthrene. Soil moisture and rhamnolipid concentration are two major factors affecting this effect. High moisture content and FTC frequency could lead to lower desorption in the early stage of FTCs due to the increased specific surface area. The sequestration of phenanthrene was less effectively hindered under seasonal FTCs than diurnal FTCs. The results from this study have important implications for understanding the role of surfactants in cold-region soil aging, and for the improvement of site remediation strategies of PAH contaminated soil in cold regions.